Better Regulation for Higher Growth : Bulgaria's Business Regulation - Achievements and Recommendations - World Bank (World Bank, 2012)
Removing regulatory obstacles that create barriers to business is a major objective for economic policymakers. There is broad understanding among policymakers and development practitioners that microeconomic reforms aimed at strengthening property rights, unleashing competition, and reducing the cost of doing business are critical to creating a sound investment climate and promoting economic growth (World Bank 2004; World Bank 2005; Lewis 2004). It is also commonly agreed that these changes need to be credible and sustained for private firms to respond by increasing investment and production (World Bank 2005). This report summarizes the findings of three topical studies of the World Bank: Administrative and Regulatory Barriers to Business (volume two) studies the overall burden of regulation for companies in comparison to other new European Union (EU) peers and specifically assesses Information Technology (IT) and manufacturing companies and the role of key stakeholders. The ex-post impact assessment of the act on limiting administrative regulation and administrative control on economic activity (Volume three) makes an assessment of how the act has been enforced, identifies and estimates the impacts of the act, and provides recommendations for amendments. Reforming the regime of state fees (volume four) examines how reforms to the structure of state fees could decrease the regulatory burden for firms.